Synthesis and Antibacterial Activity of 6-(H/Br)-7-Ethoxy Flavone - Barot, V.M. (Asian Journal of Chemistry, 2010)
6-(H/Br)-7-ethoxy flavones have been synthesized by the condensation of 2' -hydroxy-4' -ethoxy-5' -(H/Br)-chalcone with dimethyl sulphoxide (DMSO) in the presence of catalytic amount of iodine. The structures of the compounds have been supported by elemental analysis and spectral data. These compounds were screened for antibacterial activity against S. aureus and E. coli.